Learning technical words through L1 and L2: Completeness and accuracy of word meanings. (July 2015) - Gablasova, Dana
Abstract: This paper investigates the quality of knowledge of technical words that high-school students learned from subject reading. In particular, it focuses on similarities and differences between students who learned new words through their L1 and their L2. In the study, 72 students were divided into two groups and asked to read and listen to two expository texts. One group received the texts in their L1 (Slovak) and the other group in their L2 (English). Afterwards the participants were tested on their knowledge of twelve technical words that appeared in the texts. The responses were examined in terms of the completeness of word meaning and the presence of errors. The results showed that compared to the L1-instructed students, the L2-instructed participants provided word meanings that were less complete and less precise. Word meanings from both groups contained errors involving omission of correct meaning components and inclusion of incorrect meaning components. L2-instructed participants made more errors of both kinds. The differences between the two groups are discussed with respect to vocabulary acquisition and subject learning. Highlights: Learning of technical words through L1 and through L2 was compared. Understanding of newly acquired technical words was described. Two types of errors in the knowledge of meanings of technical words were identified. Similarities/differences in lexical learning through L1 and L2 were described. Differences in learning of terms by L1- and L2-instructed learners are discussed.